Nanosafety evaluation through feces: A comparison between selenium nanoparticles and selenite in rats. (February 2021) - Lin, Xiaoying; Wang, Liming; Zhao, Jiating; He, Lina; Cui, Liwei; Gao, Yuxi; Chen, Chunying; Fan, Yuqin; Li, Bai; Li, Yu-Feng
Graphical abstract: Nanosafety evaluation is necessary not only for nanomaterials R&D but also as a cornerstone for legal regulation. In this study, we proposed a non-invasive method for nanosafety evaluation using Se 0 NPs and Na2 SeO3 as examples. 16S rRNA and LC–MS were used to compare their impacts on intestinal microbiota and metabolites in fecal samples, which agreed well with their toxicity. ICP-MS, XRF and XAS were used to confirm these results. This method may also be used for the screening of the nanosafety of other nanomaterials. Highlights: A non-invasive method for nanosafety evaluation using fecal samples was proposed. Combined metagenomics and metabolomics can detect the distinct difference between Se 0 NPs and Na2 SeO3 . Metallomics and pathological analysis further confirmed the difference. This method has the potential for nanosafety evaluation of other emerging nanomaterials. Abstract: Nanosafety evaluation is necessary not only for nanomaterials research and development but also as a cornerstone for legal regulation. In this study, we proposed a non-invasive protocol for nanosafety evaluation through feces using metagenomics and metabolomics together with metallomics. Male SD rats were orally exposed to equal amounts of Se (Se 0 NPs, 3.14 or Na2 SeO3, 6.28 μg/kg bw) and were sacrificed after 24 h. 16S rRNA analysis and LC–MS were used to study the impact of different forms of Se on intestinal microbiota and metabolites in fecal samples. ICP-MS and synchrotron radiation X-ray fluorescence (SR-XRF) and X-ray absorption spectroscopy (XAS) were used to study the concentration and transformation of Se in gastrointestinal track and feces. It was found that Se 0 NPs brought less alternation to the composition of intestinal microbiota and metabolites related to inflammation, immunity and gut-brain axis related responses than Na2 SeO3 did. Besides, the absorbed Se 0 NPs could be more efficiently converted to organic Se which explained the comparable bioavailability to Na2 SeO3 . In all, the proposed protocol combined with metagenomics, metabolomics and metallomics in this study can be used for nanosafety evaluation in a non-invasive manner and this may also be used for the screening of the nanosafety of other nanomaterials.